2005
DOI: 10.1017/s0003055405051713
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering Evidence of Conditional Party Government: Reassessing Majority Party Influence in Congress and State Legislatures

Abstract: T his paper aims at enriching the debate over the measurement of majority party influence in contemporary American legislatures. Our use of a new analytic technique, a grid-search program for characterizing the uncovered set, enables us to begin with a better model of legislative proceedings that abandons the simple one-dimensional spatial models in favor of the more realistic two-dimensional version. Our conclusions are based on the analysis of real-world data rather than on arguments about the relative merit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 24 publications
0
40
0
Order By: Relevance
“…Previous work (BJS 2004) has shown that uncovered sets are rarely single points and more often sets of points. Accordingly, we implement the technique used in analyses of party influence in the U. S. House (Bianco and Sened 2005) and measure the distance between an MP and the chamber's and party's uncovered sets in terms of the average Euclidean distance between the MP's ideal point 14 The response rate was 43% for the 1987 Parliament, so we had to impute the policy positions of 368 MPs. The situation was improved for each subsequent Parliament.…”
Section: Calculating the Party Uncovered Setsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work (BJS 2004) has shown that uncovered sets are rarely single points and more often sets of points. Accordingly, we implement the technique used in analyses of party influence in the U. S. House (Bianco and Sened 2005) and measure the distance between an MP and the chamber's and party's uncovered sets in terms of the average Euclidean distance between the MP's ideal point 14 The response rate was 43% for the 1987 Parliament, so we had to impute the policy positions of 368 MPs. The situation was improved for each subsequent Parliament.…”
Section: Calculating the Party Uncovered Setsmentioning
confidence: 99%
“…In contrast, any test of the party government hypothesis under realistic assumptions about backbenchers' preferences demands that we start with a measurement tool that accounts for the collective nature of these preferences. To solve this problem, we rely on the uncovered set (Miller 1980;McKelvey 1986;Bianco, Jeliaskov, and Sened [BJS] 2004; Bianco and Sened 2005;Miller 2007) to define the collective policy preferences of British Labour and Conservative backbenchers over multiple policy dimensions. Our reliance on the uncovered set is a significant departure from the party-as-unitary-actor assumption that characterizes much of the literature on parliamentary government (Laver 2006).…”
mentioning
confidence: 99%
“…Empirically, legislative studies have observed an off-median partisan bias in voting behavior in parliament and legislative outcomes (for example, Bianco and Sened, 2005;Richmann, 2011). The literature tends to attribute this type of bias to three types of mechanisms:…”
Section: Governmental Parties' Capacity and Interest In Shaping Policiesmentioning
confidence: 99%
“…Parties' agenda-setting power: Further authors argue that parties do not need to pressure their MPs with mechanisms of party disciplines in order to ensure party loyalty. This line of reasoning sees parties as 'procedural coalitions' (the procedural cartel theory developed in Cox and McCubbins, 2005, Chapter 10; see also Bianco and Sened, 2005): given the collective benefits retired from being member of their party, MPs may accept to provide the party leadership with the control of the legislative agenda -for instance through the practice of government bills or through the creation of a policy committee with gatekeeping powers. The capacity to prevent the agenda setting of bills that divide the majority party (negative agenda power) and to push legislation over the preferred bills (positive agenda power) allows the ruling party to pass legislation that is substantially closer to their caucus' position than from the floor median position.…”
Section: Governmental Parties' Capacity and Interest In Shaping Policiesmentioning
confidence: 99%
“…Whether preferences are defined over policy outcomes or public positions is unclear, and the meaning likely varies by application. Work focused on the representation of interests and constituents (e.g., Bartels 1991, Ansolabehere et al 2001, Bafumi & Herron 2010) typically requires only that ideal points reflect legislators' public positions, but some assume that ideal points characterize true preferences over policy outcomes (e.g., Chiou & Rothenberg 2003, Bianco et al 2004, Bianco & Sened 2005.…”
Section: What Is An "Ideal" Point?mentioning
confidence: 99%